The Essentials of Georgia's Economic Transformation - Iashvili, Tsotne (University of Wroclaw. Faculty of Law, Administration & Economics, 2019)
The aim of this article is to examine Georgia's economic transformation and try to answer the question: Why Georgia is not able to have a stable and high economic growth? In this article, it will be an attempt to answer this question by taking into account the weak private sector in Georgia, as one of the main burdens of economic growth. The article attempts to analyse the economic transformation in Georgia. The reasons for its failure and consequences, also to estimate its possible impact on the nowadays economic situation in Georgia. The latter will be examined from the perspective of Institutional Theory. The article will try to answer the above-mentioned question and problems, taking into account the institutional changes in Georgia. The article explains the unsuccessful path of transformation and tries to connect its results to the current economic situation in Georgia.
Keywords: transformacja gospodarcza; transformacja postsowiecka; ekonomia instytucjonalna; Gruzja